Generalization of Dürer’s Magic Square and New Methods for Doubly Even Magic Squares - Miranda, Lohans de Oliveira; Miranda, Lossian Barbosa Bacelar (Journal of Nepal Mathematical Society, 2020)
We have established new general methods of building of doubly even magic squares and from these methods we naturally obtain Dürer's magic square. This allows us to define Dürer's magic squares for orders greater than four.